Development of Office Building Asset Management’s Standard for Public Works Highway in Kabupaten Jember - Novi Arifiani; Hitapriya Suprayitno; Retno Indryani (IPTEK Journal of Proceedings Series, 2017)
Government spends a lot of money in infrastructure, including buildings. And it increases by years. Therefore, a research to formulate how to well manage our public building is needed. The method of this research is formulating Standard Building Assets Management which can be rationally implemented  in The Office of Public Works Highway in Jember. It should be based on the theory of asset management, the ministrial regulations and best practise guideline of Queensland government building. The results of this study is the cycle of building asset management. These are Planning, Procurement, Administration (Registration and Sertification of assets), Management in Use (Assesment, Operation and Maintenance) and Disposal.